Primary Ewing Sarcoma of Kidney in an Adult: An Oddball (Indian Journal of Case Reports, 2024)
Ewing sarcoma (ES) is a malignant bone and soft-tissue tumor derived from neuroectoderm. It occurs, mostly, in pediatric adolescents with the histopathological features of invasiveness. The occurrence of ES of the kidney is rare, comprising only 1% of all renal tumors which are limited to case reports and small case series. Herein, we report a case of a 44-year-old male patient, presenting with the right flank pain and hematuria. Computed tomography scan demonstrated a right midpolar exophytic renal mass with intraluminal right renal vein and inferior vena cava (IVC) thrombus without visceral metastasis suggesting the diagnosis of renal cell carcinoma (T3BN0M0). The patient underwent the right radical nephrectomy with IVC thrombectomy. In view of the aggressiveness of the tumor, the patient received adjuvant chemotherapy (i.e., four cycles of vincristine, adriamycin, and cyclophosphamide alternating every 3 weeks with four cycles of ifosphamide and etoposide). The patient had near-complete resolution of the tumor with no thrombus seen in the follow-up scan. We could not complete six cycles of chemotherapy which were planned initially due to recurrent cytopenias. Six months postchemotherapy, the patient is clinically and radiologically disease-free and is in close follow-up. We are reporting this case to highlight the rarity of this entity and its challenging clinicopathological diagnosis when presenting as a renal tumor.